Reviewing and Responding to the Thought of Choan-Seng Song (Occasional bulletin of missionary research, 1977)
Choan-Seng Song, formerly Professor of Theology and Principal of Tainan Theological College in Taiwan and now Associate Director of the Commission on Faith and Order of the World Council of Churches in Geneva, is among the most stimulating of present-day Asian theologians. Dr. Song has become increasingly well known to missiological circles in North America through his service as a visiting professor at Princeton Theological Seminary during the academic year 1976–77. His book Christian Mission In Reconstruction: An Asian Attempt was first published in Madras by the Christian Literature Society of India in 1976. Orbis Books has scheduled an American edition to appear in the fall of 1977.The Occasional Bulletin of Missionary Research invited D. Preman Niles, Professor in the field of Biblical Studies at the Theological College in Pilimatalawa, Sri Lanka, and Charles C. West, the Stephen Colwell Professor of Christian Ethics at Princeton Theological Seminary in New Jersey to write brief articles on “Reviewing and Responding to the Thought of Choan-Seng Song.” Although Dr. Song's recent book is intended to be a particular focus of those two reflections, they go beyond it to a wider consideration of his theological thought. In turn, Dr. Song was invited to submit a “reaction-to-the-reactions.” The three articles follow in that order.